(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A library is considered as the ’heart’ of an educational institution and it is the centre of learning for primary to higher education system. Due to the COVID-19 pandemic, the library operation has been restrained due to safety issues of the users and library staffs. A questionnaire survey was carried out using Google Form virtual platform from the top administrators of the libraries spread over India. Around 138 responses were received during the survey. The survey data were collected in Google spreadsheet and stored in MS Excel platform for further analysis. The normal precaution measures such as social distancing, using sanitizer and face mask etc. need to be followed during library operation. The use of face shield, head cover, PPE kit etc. may be provided for the front desk and security personnel. The return books should be sanitized through isolation, UVC box technique, and home delivery system may be used during the pandemic. The vast virtual resources and online classes etc. should be explored and may be channelized to the users through libraries. The remote access of library and other resources login password, remoteXs service, IP authentication etc. may be allowed to users for reducing frequent visit to the library. The virtual resources can also be created at the library by the faculty members of the university for their students and users. Online examination and evaluation may be promoted by the libraries during the pandemic situation.The library floor design may be revised to maintain space between the users using mobile reading table with acrylic separation bars, acrylic sneeze guards, desk separators, front desk barriers, cough screens etc. in the library.